Political Linguistics as a Basis of Political Speech - Rakhmatovna, Boltayeva Nargiza (Researchparks Publishing, 2023)
In the given article political linguistics is studied as a fundamental method of political text and political speech. Political knowledge is a basic source of political study that is related to all subjects. In this article the full information is given about political linguistics. The aim of this article is to give information to students how the relations link between politics and language and connection with other subjects in every sphere of the world.